2020
DOI: 10.1002/ldr.3781
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alfalfa and NPK fertilization in agricultural reclamation on the transformation of Technosols in an area following lignite mining

Abstract: Open‐cast mining of lignite leads to considerable degradation of the natural environment, which then must be reclaimed. The aim of this study was to assess the transformation of Technosols in an area after lignite mining which had been under 40‐year cultivation of alfalfa with grass at various NPK fertilization rates. We hypothesized that 40‐year cultivation of plants caused morphological transformation of the parent material and resulted in differentiation of physical and chemical properties in the profile of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…NPK-fertilized coal mine spoils which were under legume (Medicago sativa) and grass (Dactylis glomerata) revegetation for 40 years demonstrated 18% more total N compared with control. The authors concluded that grasslegume seeding plays a primary role in the reclamation processes, while NPK fertilizer application plays a supporting role (Otremba et al, 2020). 4.1.4 | Topsoil amendment Amendments like topsoil have been considered extensively in mine-degraded areas where the native soil is badly damaged.…”
Section: Inorganic Amendmentsmentioning
confidence: 99%
“…NPK-fertilized coal mine spoils which were under legume (Medicago sativa) and grass (Dactylis glomerata) revegetation for 40 years demonstrated 18% more total N compared with control. The authors concluded that grasslegume seeding plays a primary role in the reclamation processes, while NPK fertilizer application plays a supporting role (Otremba et al, 2020). 4.1.4 | Topsoil amendment Amendments like topsoil have been considered extensively in mine-degraded areas where the native soil is badly damaged.…”
Section: Inorganic Amendmentsmentioning
confidence: 99%
“…This soil management technique has been used to reclaim degraded soils in microcosm studies (Abreu & Magalhães, 2009; Cortinhas et al, 2020; Cortinhas et al, 2021; Fourvel et al, 2019; Macía et al, 2014; Otremba et al, 2021) and field, in mining context (Arán et al, 2021; Asensio et al, 2013). Nonetheless, there are only a few reports on this technique applied to degraded Mediterranean estuarine environments (Cortinhas et al, 2020; Cortinhas et al, 2021), and none of them approach succulent halophytes cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Tailored soils construction is a sustainable technology that allows to improve the physical (e.g., aggregation), chemical (e.g., nutrients concentration), and biological (e.g., soil biota) soil properties (Santos, Abreu, Macías, & Magalhães, 2017;Séré et al, 2010). This soil management technique has been used to reclaim degraded soils in microcosm studies (Abreu & Magalhães, 2009;Cortinhas et al, 2020;Cortinhas et al, 2021;Fourvel et al, 2019;Macía et al, 2014;Otremba et al, 2021) and field, in mining context (Arán et al, 2021;Asensio et al, 2013). Nonetheless, there are only a few reports on this technique applied to degraded Mediterranean estuarine environments (Cortinhas et al, 2020;Cortinhas et al, 2021), and none of them approach succulent halophytes cultivation.…”
mentioning
confidence: 99%
“…Natural succession frequently fails to successfully reestablish the vegetation cover in sites heavily disturbed by mining (Ruggles et al, 2021) or occurs at slower rates than expected due to poor substrate conditions (Gilland & McCarthy, 2014). In mining waste deposits, active reclamation is often necessary to ensure a transformation of the mining waste into Technosols (“soils dominated or strongly influenced by human‐made material”; IUSS, 2014; Schad, 2018) and restore its utility or environmental value (Otremba et al, 2021). In Colombia, several approaches have been developed to reclaim dredged‐sediment landfills resulting from alluvial gold mining activities through reforestation and agroforestry (Castellanos Barliza & Leon, 2010; Mosquera et al, 2008; Thomas, 2014).…”
Section: Introductionmentioning
confidence: 99%